108+4x=-92-6x

Simple and best practice solution for 108+4x=-92-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 108+4x=-92-6x equation:


Simplifying
108 + 4x = -92 + -6x

Solving
108 + 4x = -92 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
108 + 4x + 6x = -92 + -6x + 6x

Combine like terms: 4x + 6x = 10x
108 + 10x = -92 + -6x + 6x

Combine like terms: -6x + 6x = 0
108 + 10x = -92 + 0
108 + 10x = -92

Add '-108' to each side of the equation.
108 + -108 + 10x = -92 + -108

Combine like terms: 108 + -108 = 0
0 + 10x = -92 + -108
10x = -92 + -108

Combine like terms: -92 + -108 = -200
10x = -200

Divide each side by '10'.
x = -20

Simplifying
x = -20

See similar equations:

| D=20+60h | | 45=7-5 | | 2.25(4x-4)=2.3d+3 | | 5(m-1)-2m=16 | | k+19=3+5k | | 2z^3=10z | | 14p-4-6p=26 | | .5x-.5(2x+3)=-.6(x+4) | | 9r-6-6t=6 | | 7x+4x-38=57-8x | | 9x^8-148x^4+64=0 | | -3(2y-3)-y=-4(y-5) | | 7x+8x-10=180 | | 32+2b=22 | | p-1=37+13p-14p | | .7x-.2(13-4x)=-.1(x-6) | | -3(5n-4)=8n+2 | | 5x+40=5x+40 | | 50x-40y= | | x^2+y^2+4x-6y-2=0 | | 5(c-8)=20 | | y+12xy=0 | | 5(v+1)=7(1+v) | | 12p+6+4p=24 | | 200m-125m+47500=50250-175m | | 12y+2(-11y-6)=-232 | | 19.95+99x+65.32=144.67 | | 2p+2q-6(2p-3q+4r)= | | (3x^2+4x-1)+(2x^2-3x+2)=0 | | 6m-8=24 | | n/17+571=596 | | 4n^2-21n-20=0 |

Equations solver categories